STRUKTUR CERITA RAKYAT BUAYA KUNING - Rizky Purwanti; Chairil Effendy; Martono Martono (Universitas Tanjungpura, 2022)
The purpose of this study is to describe the structure of the Yellow Crocodile folklore. In particular, this research reveals the themes, characters, characterizations, setting, and plot. This study uses a qualitative descriptive method with a structural approach to analyze the intrinsic elements in the Buaya Kuning folklore so this research uses a documentary study technique. The results showed that the theme in the story of the Yellow Crocodile was keeping the vows spoken. The characters and characterizations in this story are Raja Kodung (easy to give up and keep promises), the king's bodyguard (faithful) and Putri Banyu Mustari (polite and sincere). The background used is the setting of place, time, and socio-cultural. The plot in this story is a forward plot. In conclusion, in everyday life it is necessary to have an attitude to always keep the promises that have been made because in society this attitude makes it easy for people to give trust.